Toolkit for adapting community engagement studios to effectively engage older adults in research - Shaye A. Kerper; Janelle C. Christensen; Steven M. Albert (Journal of Clinical and Translational Science)
Older adults have largely been excluded from health research despite bearing a disproportionate disease burden. The Community Engagement Studio (CES) model, initially developed at Vanderbilt University in 2009, allows potential research participants to help shape research to promote greater inclusion. The University of Pittsburgh adapted the CES model for older adults (OA-CES). Tailored specifically to older adults, OA-CES addresses underrepresentation in research by gathering valuable feedback that allows investigators to make research more accessible and relevant to older people. An OA-CES toolkit will help in adapting the model in other research areas to close the gap in research inclusion.